Connecting cities addressing the issue of divided cities through environmental graphic design - Ramirez, Abigeal D. (College of Architecture, University of the Philippines Diliman, 2019)
Together with developments, barriers arise between communities creating a division which can be caused by several factors. Frequently, these are intangible barriers. This is where the importance of environmental graphic design or EGD comes in. As cities continue to develop, the need for a communication system increases. These continue to develop, the need for a communication tools are extremely helpful when it comes to navigating various spaces be it a building, a building complex, a small district or even a whole city. These visual communication tools not only provide information but they serve as the link between the user and the space in which they navigate. According to past studies, encouraging cross-participation between cities yield positive effect both economically and socially. To be able create this connection, a communication process is needed. It is important to note that designers can merely create the medium to which this communication can be expressed, but only the receivers of this "language" can give meaning to it placing the importance on how the users perceive a space rather which can be further enhanced through designing the physical environment.